1968
DOI: 10.2151/jmsj1965.46.5_327
|View full text |Cite
|
Sign up to set email alerts
|

Time Sequence of Power Spectra of Disturbances in the Equatorial Lower Stratosphere in Relation to the Quasi-Biennial Oscillation

Abstract: A power spectral analysis is made for the data of upper winds at Canton Island (S 02°46", The vertical extent of the disturbances is roughly 4 km on the average. The phase of the disturbances at lower levels lags behind that at upper levels. The phase lines of the disturbances tilt westward with height, in consideration of their westward propagation supported by additional synoptic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 9 publications
(9 reference statements)
10
48
0
Order By: Relevance
“…These longitudinal waves were identified with the Kelvin waves whose existence had also been predicted in Matsuno's theory (1966). Maruyama (1969) confirmed the existence of the 10-to 15-day period as well as of the 4-to 5-day period in the spectra of the 50-mb winds of Canton Island. Wallace and Change (1969) found that a 10-to 15-day periodicity is pronounced also in the lower tropospheric levels especially in the zonal component.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…These longitudinal waves were identified with the Kelvin waves whose existence had also been predicted in Matsuno's theory (1966). Maruyama (1969) confirmed the existence of the 10-to 15-day period as well as of the 4-to 5-day period in the spectra of the 50-mb winds of Canton Island. Wallace and Change (1969) found that a 10-to 15-day periodicity is pronounced also in the lower tropospheric levels especially in the zonal component.…”
Section: Introductionsupporting
confidence: 67%
“…Maruyama (1967) and Lindzen and Matsuno (1968) identified the observed waves as mixed Rossbygravity waves which were obtained in the theory of equatorial waves (Rosenthal, 1965;Matuno, 1966;Lindzen, 1967). Further studies of Maruyama (1968 b) and Yanai and Hayashi (1969) established that these planetary-scale waves carry both westerly momentum and wave energy upward and the sensible heat poleward.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Maruyama (1968a), using the data from Canton Island (2.8S, 171.7W) for the three year period from June 1957 to May 1960, presented a time sequence of the power spectra of the meridional wind component as it relate to the QBO. The sequence showed that the power density at a period of about 4 days increased when the absolute value of the mean wind speed decreased.…”
Section: Introductionmentioning
confidence: 99%